Injury epidemiology of tennis players at the 2011–2016 Australian Open Grand Slam. Issue 17 (7th July 2017) - Gescheit, Danielle T; Cormack, Stuart J; Duffield, Rob; Kovalchik, Stephanie; Wood, Tim O; Omizzolo, Melanie; Reid, Machar
Abstract : Aim: To examine the epidemiology and in-event treatment frequency of injury at the 2011–2016 Australian Open tournaments. Methods: Injury incidence was defined as a medical consultation by a tournament physician and in-event treatment frequency as the mean total number of follow-up medical/physiotherapy consultations (2013–2016 tournaments only). Data were collated by sex, injury region and type and reported as frequencies per 10 000 game exposures. Incidence rate s± 95% CI and rate ratios were used to test effects for injury, sex and year. Results: Female players experienced more injuries than male players (201.7 vs 148.6). The shoulder (5.1±1.1 injuries per year), foot (3.2±1.1), wrist (3.1±1.5) and knee (3.1±1.1) were the most commonly injured regions among females. Knee (3.5±1.6), ankle (2.3±1.3) and thigh (2.3±1.5) were the most prevalent male injuries. Upper arm injuries and in-event treatment frequency increased by ≥2.4 times in both sexes over the 5-year period. Muscle injuries were most frequent. There was a greater than twofold increase in men and women with stress fractures over the 5-year period. The torso region, including the neck, thoracic spine, trunk and abdominal, lumbar spine, hip and groin, pelvis/buttock, attracted high in-event treatment frequencies in both sexes. Conclusion: Investigation of injury at the Australian Open suggests that females are more commonly injured than males. Upper and lower extremity injuries affected females while lower limb injuries were more prominent in males. There was an increasing rate of in-event treatments of upper limb and torso injuries as well as stress fractures during the observation period.